Plus : Servicepunt Hiv Vereniging Nederland. (Amsterdam : HIV Vereniging Nederland, 2000)
Fonds Suzan Daniel (FSD)
Periodiciteit: tweemaandelijks
Redactie: PB 15847, 1001 NH Amsterdam
Nederlands
Periodiek